The concept of love based curriculum management in Madrasah Ibtidaiyah (MI) - Dedi Sahputra Napitupulu; Mursal Aziz; Rita Novita Sari Panjaitan (At Turots: Jurnal Pendidikan Islam, 2025)
This study aims to examine the concept of love based curriculum management in Madrasah Ibtidaiyah (MI), focusing on three main aspects: curriculum planning, implementation, and evaluation. The research employed a literature review method by analyzing books, scientific journals, articles, and official documents relevant to curriculum management and Islamic education. The findings reveal three key results. First, in the planning aspect, the curriculum is designed by integrating values of compassion into the learning objectives, material selection, and strategies for developing children's potential. This approach seeks to create a learning environment that emphasizes not only cognitive development but also affective and spiritual dimensions. Second, in the implementation aspect, the lovecbased curriculum is manifested through participatory, dialogical, and exemplary teaching methods, in which teachers serve as compassionate figures capable of motivating and personally guiding students. Third, in the evaluation aspect, the approach adopted is more appreciative, motivational, and constructive, highlighting character development and children's social skills rather than solely academic achievement. The study concludes that lovecbased curriculum management can offer a humanistic and holistic model of Islamic education that aligns with the needs of learners in the modern era. Thus, this concept may serve as an alternative paradigm for strengthening the quality of Islamic primary education in Madrasah Ibtidaiyah.